Effectiveness of Discipleship in Building Self-Concept of Ex-Convicts - Rumalutur, Selfilin (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Ex-convicts in Indonesia faced significant social stigmatization that hindered their reintegration into society and negatively impacted their self-concept. This study examined the effectiveness of Christian discipleship programs in developing positive self-concept among ex-convicts. The research was conducted at GKIN